Propagation challenges in 5G millimeter wave implementation - Siti Fatimah Nordin; Zuhanis Mansor; Aizat Faiz Ramli; Hafiz Basarudin (Institute of Advanced Engineering and Science, 2019)
With current technology advances, implementing millimeter wave in real life have become more promising. However, before millimeter wave can be deployed, there are several challenges in terms of technical, path loss and shadowing. This paper provides a review on the challenges that might occurs when implementing millimeter wave. An overview of LTE-Advanced and millimeter wave is made to provide further understanding. A critical analysis is made to identify the problem in rain and haze attenuation, if addressed, will help mobile service provider to overcome the problem.